2015
DOI: 10.3906/biy-1412-76
|View full text |Cite
|
Sign up to set email alerts
|

Storage temperature of boar semen and its relationship to changes in sperm plasma membrane integrity, mitochondrial membrane potential, and oxidoreductive capability

Abstract: The aim of this study was to analyze changes in sperm plasma membrane integrity, mitochondrial activity, and extracellular environment during storage of boar semen at 5 °C, 16 °C, and 25 °C for 10 days. Progressive sperm motility, plasma membrane integrity (SYBR-14/PI-test and HOS test), aspartate aminotransferase (AAT), and mitochondrial activity (JC-1-test and NADH-dependent NBT assay), as well as pH and osmolality were assessed in nine ejaculates of Polish Landrace boars. The plasma membrane integrity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 58 publications
1
18
0
5
Order By: Relevance
“…Liquid preservation of boar sperm under hypothermic conditions, 5°C, may be connected with alterations in the plasma membrane stability and disorders of mitochondrial transmembrane potential and oxidoreductive capability affecting the sperm motility (Gączarzewicz, Udała, Piasecka, Błaszczyk, & Stankiewicz, ). However, the supplementation of commercial extenders with ostrich egg yolk lipoproteins seemed to improve the metabolic efficiency of boar spermatozoa during storage for 3 days at 5°C (Dziekońska, Kinder, Fraser, Strzeżek, & Kordan, ).…”
Section: Temperaturementioning
confidence: 99%
“…Liquid preservation of boar sperm under hypothermic conditions, 5°C, may be connected with alterations in the plasma membrane stability and disorders of mitochondrial transmembrane potential and oxidoreductive capability affecting the sperm motility (Gączarzewicz, Udała, Piasecka, Błaszczyk, & Stankiewicz, ). However, the supplementation of commercial extenders with ostrich egg yolk lipoproteins seemed to improve the metabolic efficiency of boar spermatozoa during storage for 3 days at 5°C (Dziekońska, Kinder, Fraser, Strzeżek, & Kordan, ).…”
Section: Temperaturementioning
confidence: 99%
“…The pH of the semen samples was measured using a two-point calibrated (pH 6.0 and 8.0; Poch, Poland) pH-meter (CP-315M, Elmetron; electrode type ERH-13-6, Hydromet, Poland). The measurement of aspartate aminotransferase (AAT; EC 2.6.1.1) activity was used to determine the changes in sperm plasma membrane integrity during storage (Gączarzewicz et al, 2015). Enzyme activity was assessed by the kinetic method according to the manufacturer's protocol (A6461, Alpha Diagnostics, Poland).…”
Section: Semen Evaluationmentioning
confidence: 99%
“…Interestingly, no differences between fractions were observed after the use of the SCP extender, which suggests that the choice of extender is essential. When the ejaculate fraction is diluted with an extender, the effect of seminal plasma on spermatozoa is significantly limited, and prolonged storage in an extender modifies the structural and functional characteristics of sperm cells (Garcia et al 2009, Gączarzewicz et al 2015. Our study demonstrated that the quality of stored spermatozoa is affected not only by ejaculate fraction but also significantly by the type of extender.…”
Section: Discussionmentioning
confidence: 47%